British teachers' transnational work within and beyond the British Empire after the Second World War. Issue 3 (4th May 2017) - Whitehead, Kay
Abstract: Focusing on British graduates from Gipsy Hill Training College (GHTC) in London, this article illustrates transnational history's concerns with the reciprocal flows of people and ideas within and beyond the British Empire. GHTC's progressive curriculum and culture positioned women teachers as agents of change, and the article highlights the lives and work of married and single graduates overseas after the Second World War. Some migrated to the dominions of Australia, Canada and New Zealand, while South Africa and Southern Rhodesia (Zimbabwe) were popular destinations for short-term teaching contracts. A few graduates went to the colonies as missionaries and colonial servants, and a handful taught in extra-imperial sites. Wherever they were located, these British women promulgated the college's progressive ideals and shared their experiences with people at home in Britain, thereby shaping understandings of the Empire and constructing a world that was differentiated by class, gender, race and nation.